Efek eugenol terhadap jumlah sel inflamasi pada pulpa gigi molar tikus Sprague Dawley - Raras Ajeng Enggardipta; Tetiana Haniastuti; Juni Handajani (Majalah Kedokteran Gigi Indonesia, 2016)
Inflammatory cells infiltration after eugenol administration in Sprague Dawley rat’s molars. The purpose of this study was to determine effect of eugenol on inflammatory cells infiltration (neutrophils, macrophages and lymphocytes) in the inflamed dental pulp. Thirty male Sprague Dawley rats aged 3-4 months and weighed 300-350 g were randomly divided into 2 groups: treated and control groups. Rats were injected with ketamine HCl i.m. (0.1 ml/100 grams BW) before cavity preparation at occlusal surface of the upper molars. Cavity preparation was made using a round bur No.010 to pulp perforation. At the cavity base of treated group, 15 rats were given eugenol and of control group 15 rats were given aquadest, before filled with temporary filling. Three rats from each group were sacrificed at 1, 3, 5, 7 and 14 days after the cavity preparation. Rats were injected with ketamine HCl im (0.1 ml / 100 g BW) on the thigh then tissues were collected for histological process and stained using haematoxylin eosin. The number of inflammatory cells (neutrophils, macrophages and lymphocytes) was analysed by Two-Way Anova. The result of the study showed number of inflammatory cells infiltration of treated group was lower than control and showed significant differences between groups (p <0.05). The conclusion from this study is eugenol administration in Sprague Dawley rats’s inflamed dental pulp can reduce the number of inflammatory cells (neutrophils, macrophages and lymphocytes).ABSTRAKPenelitian ini bertujuan untuk mengetahui pengaruh eugenol terhadap jumlah sel inflamasi (netrofil, makrofag dan limfosit) pada pulpa gigi terinflamasi. Tiga puluh ekor tikus Sprague Dawley jantan berumur  3-4 bulan dengan berat badan 300-350 g dibagi secara acak dalam 2 kelompok yaitu perlakuan dan kontrol. Tikus diinjeksi ketamine HCl i.m. (0,1 ml/100 gram BB) sebelum dilakukan preparasi kavitas pada permukaan oklusal gigi molar satu rahang atas. Preparasi kavitas dibuat dengan menggunakan bur bulat No.010 hingga kedalaman pulpa. Pada dasar kavitas kelompok perlakuan (15 ekor) diberi eugenol dan kelompok kontrol (15 ekor) diberi akuades, kemudian kavitas ditumpat sementara. Tiga ekor tikus dari masing-masing kelompok dikorbankan pada 1, 3, 5, 7 dan 14 hari pasca preparasi kavitas. Tikus diinjeksi ketamine HCl i.m. (0,1 ml/100 gram BB) pada paha kemudian jaringan diambil, diproses secara histologis dan dicat dengan hematoxylin eosin. Data jumlah sel inflamasi (netrofil, makrofag dan limfosit) dianalisis dengan Two Way Anova. Hasil penelitian menunjukkan rerata jumlah infiltrasi sel inflamasi kelompok perlakuan lebih rendah dibandingkan kontrol dan berbeda bermakna (p<0,05). Kesimpulan dari penelitian ini adalah pemberian eugenol pada pulpa gigi tikus Sprague Dawley yang mengalami inflamasi dapat menurunkan jumlah sel inflamasi (netrofil, makrofag dan limfosit).